Stakeholder engagement for south-south collaboration on improved rice cultivation using geospatial sciences - Gakhar, Shalini; Mathieu, Renaud; Patwar, Shelly; Jardinero, Benedict; Sahoo, Rabi N.; Chinnusamy, Viswanathan (CGIAR Research Initiative on Digital Innovation, 2024)
Stakeholder Engagement for South-South Collaboration on Improved Rice Cultivation Using Geospatial Sciences was organized on November 14 and 15 in Mwea, Kenya. The CGIAR Initiative on Digital Innovation (DI) focuses on enabling digital innovations to stimulate the inclusive and sustainable transformation of food, land, and water systems. This includes investments that policymakers could make to close the digital divide, information delivery systems that allow more people to take action against predicted risks, and ways for partner organizations and marginalized communities to enhance digital capabilities, access resources, and seize opportunities. India has the largest area under rice cultivation in the world, covering 44.6 million hectares, and is second only to China in terms of rice production. Rice is the staple food for 65 percent of India's total population and plays a crucial role in the country's economy as a leading rice exporter.